2016
DOI: 10.1088/0741-3335/59/1/014006
|View full text |Cite
|
Sign up to set email alerts
|

Progress in understanding disruptions triggered by massive gas injection via 3D non-linear MHD modelling with JOREK

Abstract: 3D non-linear MHD simulations of a D 2 massive gas injection (MGI) triggered disruption in JET with the JOREK code provide results which are qualitatively consistent with experimental observations and shed light on the physics at play. In particular, it is observed that the gas destabilizes a large m/n = 2/1 tearing mode, with the island O-point coinciding with the gas deposition region, by enhancing the plasma resistivity via cooling. When the 2/1 island gets so large that its inner side reaches the q = 3/2 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
89
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(98 citation statements)
references
References 12 publications
8
89
0
1
Order By: Relevance
“…The physics of thermal quenches, whether naturally occurring or produced by impurity injection, has much in common [14]. The breakup of surfaces and the associated rapid thermal quench due to massive-gas or shattered-pellet injection have been seen in a number of simulations [5][6][7][8].…”
Section: Natural and Forced Surface Breakupmentioning
confidence: 99%
See 3 more Smart Citations
“…The physics of thermal quenches, whether naturally occurring or produced by impurity injection, has much in common [14]. The breakup of surfaces and the associated rapid thermal quench due to massive-gas or shattered-pellet injection have been seen in a number of simulations [5][6][7][8].…”
Section: Natural and Forced Surface Breakupmentioning
confidence: 99%
“…Non-intercepting flux tubes are seen in numerical simulations [5][6][7][8] of massive gas and shattered pellet injection-particularly near the magnetic axis and sometimes in the cores of magnetic islands. Nonintercepting flux tubes are also seen in models of the effects of non-axisymmetric magnetic fields [17,18] and are found to provide excellent confinement of relativistic electrons [17,19].…”
Section: Non-intercepting Flux Tubesmentioning
confidence: 99%
See 2 more Smart Citations
“…The effect of rotation on the asymmetry is suppressed and the effect of toroidal spreading of the impurities -due to parallel thermal velocity -is limited by the low plasma temperature in this dedicated experiment. This data-set is particularly suited for the benchmark of 3-D non-linear MHD codes, such as JOREK, which is being further developed for disruption modelling [10]. In previous experiments [11], it was found that plasmas at larger energies could not be stopped by the RMPs and therefore the radiation asymmetry was affected by a residual, difficult to measure, rotation.…”
Section: Asymmetric Radiation Distribution During the Pre-tqmentioning
confidence: 99%